Role of Thyroid Stimulating Immunoglobulins (TSI) in Early Diagnosis of Patients with Euthyroid Grave’s Ophthalmopathy: Doi:10.36351/pjo.v36i4.1113 - Idris, Mohammad; Umer, Muhammad Zubair; Nathaniel, Eemaz; Iqbal, Muhammad; Zar, Adnan (Pakistan Journal of Ophthalmology, 2020)
OBJECTIVE: to determine the role of thyroid stimulating immunoglobulin (TSI) in early diagnosis of patients with euthyroid grave’s ophthalmopathy visiting Oculoplastic service of a tertiary care centre Study design: cross sectional descriptive study Place and Duration of Study: Oculoplastic service, out patient department of ophthalmology, ——-from August 2015 to August 2016. Methodology: ninety patients of both the genders with euthyroid Greave`s Ophthalmopathy at any stage of severity of the disease by non-probability purposive sampling technique. One-way ANOVA test was also done for TSI with Age groups and Gender. RESULTS: Among 90 patients, Females were more than males, 68.9% and 31.1% respectively. 4 age groups were made in which age group of 41 – 55 years patients were more (37.8%) and after that was patients of more than 56 years of age (32.2%). 84% had their thyroid stimulating immunoglobulin (TSI) test positive. Cross tabulation was performed for TSI with Gender. 84.4% of the males and females had their TSI positive with females having more tests positive than males, 55.6% and 28.9% respectively with a p value of 0.139. CONCLUSION: TSI is positive in majority of female Euthroid Graves ophthalmopathy patients visiting Oculoplastics clinics in age having 41 – 55 years. The association of TSI with gender showed higher significance than age. Early diagnosis with the help of TSI without any expensive investigations even when other thyroid function tests are normal can prevent complications especially ophthalmopathy by timely referral to endocrinologist.